PENGARUH PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN DENGAN FILOSOFI TRI HITA KARANA - Sunarya, I.N.Manik; Cok.Gde Bayu Putra (Hita Akuntansi dan Keuangan, 2021)
The purpose of this research is to look at the influence of the various influences of Good Corporate Governance on financial performance and the influence of the Tri Hita Karana philosophy on the relationship between the various principles (principles) of Good Corporate Governance and financial performance in the LPD, Blahbatuh Gianyar District. The number of samples used was 72 people. Questionnaires are used as a way to collect data. The data analysis technique used moderated regression analysis. From the questionnaire that has shown the results of various principles (principles) of good corporate governance have a relevant influence on financial performance in the LPD, Blahbatuh Gianyar District. The Tri Hita Karana philosophy can erase the implementation of the principles of Good Corporate Governance on financial performance in the LPD, Blahbatuh Gianyar District.